2003
DOI: 10.1007/bf03021056
|View full text |Cite
|
Sign up to set email alerts
|

Systemic, but not pulmonary, hemodynamics are depressed during combined high thoraco-cervical epidural and general anesthesia in dogs

Abstract: P Pu ur rp po os se e: : An epidural block is frequently combined with general anesthesia. Both systemic and pulmonary hemodynamics may be affected by high epidural anesthesia and the combined general anesthetic. These effects were investigated in a canine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Machala et al [ 4 ] studied the hemodynamic effects of propofol, found that propofol increased the pulmonary mean arterial pressure and afterload on the right ventricle. Funayama and his group [ 5 ] combined high thoraco-cervical epidural and general anesthesia in dogs found that propofol altered neither the pulmonary mean arterial pressure nor the pulmonary vascular resistance, but did decrease systemic vascular resistance. Another study [ 6 ] compared vasorelaxation induced by propofol in the intrapulmonary artery (IPA) and tehe extrapulmonary artery (EPA) and concluded that the response was significantly greater in the EPA than the IPA at higher drug concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Machala et al [ 4 ] studied the hemodynamic effects of propofol, found that propofol increased the pulmonary mean arterial pressure and afterload on the right ventricle. Funayama and his group [ 5 ] combined high thoraco-cervical epidural and general anesthesia in dogs found that propofol altered neither the pulmonary mean arterial pressure nor the pulmonary vascular resistance, but did decrease systemic vascular resistance. Another study [ 6 ] compared vasorelaxation induced by propofol in the intrapulmonary artery (IPA) and tehe extrapulmonary artery (EPA) and concluded that the response was significantly greater in the EPA than the IPA at higher drug concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic epidurals have been associated with decreased sympathetic tone (9,10) with a negative influence on cardiac output (11,12) but enhanced blood flow to the blocked region (13). Blood flow to the vagina is regulated by thoracolumbar sympathetic nuclei via the hypogastric nerve (14).…”
mentioning
confidence: 99%